Physical and technical performance of elite youth soccer players during international tournaments: Influence of opponent quality and team success - Varley, M.; Gregson, W.; McMillan, K.; Bonnano, D.; Stafford, K.; Modonutti, M.; Di Salvo, V. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: This study investigated the positional differences in physical performance of elite youth footballers across two international club tournaments and the influence of team success and opponent quality on team physical and technical performance. Method: Match performance observations were collected using a semi-automated multi-camera tracking system across two elite under-17 international club tournaments from all players and teams (n=1,457 individual cases). To investigate if the exclusion of substituted players influenced the physical performance profile, data of only players who completed a full game and data of all players were analysed in relative (m.min-1) terms. Teams were classified based on their final tournament rank as top (1-4 rank), middle (5-8 rank) and bottom (9-12 rank). Technical performance measures were expressed in absolute terms and relative to the time the team was in possession of the ball. Positional differences in physical performance and the influence of team success and opponent quality on team match performance were identified using a generalized linear mixed model. Results: Positional differences were similar to that observed in elite senior players. Full game players experienced a clear reduction in relative very-high speed running distance in the 2nd half, however when all players were analysed there were no clear reductions. Top ranked teams performed a greater number of absolute and relative shots and shots on target than bottom teams (Effect Size = 0.67 to 0.82). Passing and organising variables had unclear effects between team rankings. Top ranking teams performed a greater number of relative tackles than bottom and middle teams (ES; 0.44 to 0.70). When playing against top ranking opponents the number of absolute shots and shots on target, shot conversion and passing accuracy were lowest compared to playing against middle and bottom opponents (ES; -0.86 to -0.31). Discussion: In an elite youth tournament setting, opponent quality has a greater influence on match performance than team success. Practitioners should account for these contextual factors when analysing match performance data to assist in their match preparation. Finally, match analysis should include full game players and all players to avoid to understand the influence of substitutes on team physical performance.